Complex rehabilitation and therapeutic care involving a polytraumatized patient with traumatic brain injury, cervical spinal cord injury and multiple associated lesions - case report - Mihai Băilă (Balneo Research Journal, 2018)
The subject matter of the present scientific paper is the report of the therapeutic and rehabilitation program of a polytraumatized patient with severe traumatic brain injury and mild cervical spinal cord injury, that led to serious functional consequences: psychocognitive, neuromotor, neurosensitive and autonomous.